A religião e a religiosidade e os seus impactos no comportamento ético do consumidor. - Morais, Thaís de Matos Barbosa Nunes (2012)
The present work has as objective to analyse how religion/religiosity, as well as its impacts, and how those constructs can generate reactions positive or negatives ones in consumers behaviour. It is also being observed if there is a possible interrelation between the consumers behaviour and their decision process. To acquire those information, a quantitative approach was adopted as a methodological procedure, through the application of a structured survey with people from João Pessoa whose objective was to verify their behaviour as well as their perception of action illegality. The survey was organized in a two-leved model: in the first level, they were asked to answer questions about religion/religiosity; and in the second level, they answered questions about consumption and ethics. The sample for this study was of 194 respondents from survey face to face and internet. Overall, the tested hypotheses were partially valid showing a distorted speech between ethical and real consumption, with religion/religiousness being a non-totally determinant during the ethical consumption decision. It was concluded that although ethical consumption discourse fills the collective imagination up, there is a considerable discrepancy between the ethical discourse and its practice while related to the consumption practices in Brazil.